Breaking bad and cinematic television - Restivo, Angelo, 1949- (Console-ing passions book series. Spin offs., 2019)
Angelo Restivo uses the innovative show Breaking Bad as a point of departure for theorizing a new aesthetics of television in which the concept of the cinematic points to the ways in which television can change the ways viewers relate to and interact with the world.